Needle-based storage-phosphor detector radiography is superior to a conventional powder-based storage phosphor detector and a high-resolution screen-film system in small patients (budgerigars and mice) - Wiebke Tebrün (Nature Portfolio, 2019)
Abstract This method comparison study used radiographs of 20 mice and 20 budgerigars to investigate comparability between computed radiography (CR) and high-resolution screen-film systems and study the effects of reduced radiation doses on image quality of digital radiographs of small patients. Exposure settings used with the mammography screen-film system (SF) were taken as baseline settings. A powder-based storage-phosphor system (CRP) and a needle-based storage-phosphor system (CRN) were used with the same settings (D/100%) and half the detector dose (D/50%). Using a scoring system four reviewers assessed five criteria per species covering soft tissue and bone structures. Results were evaluated for differences between reviewers (interobserver variability), systems and settings (intersystem variability, using visual grading characteristic analysis). Correlations were significant (p ≤ 0.05) for interobserver variability in 86.7% of the cases. Correlation coefficients ranged from 0.206 to 0.772. For mice and budgerigars, the CRN system was rated as superior to the SF and CRP system for most criteria, being significant in two cases each. Comparing the SF and CRP system, the conventional method scored higher for all criteria, in one case significantly. For both species and both digital systems, dose reduction to 50% resulted in significantly worse scores for most criteria. In summary, the needle-based storage-phosphor technique proved to be superior compared to the conventional storage-phosphor and mammography screen-film system. Needle-based detector systems are suitable substitutes for high-resolution screen–film systems when performing diagnostic imaging of small patients. Dose reduction to 50% of the corresponding dose needed in high-resolution film-screen systems cannot be recommended.